(3TQM cJGH GdaQGFV ddSQGLis - (3eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj, SQGL GdOjf CHh WGgQ,J (B598 (3g` s
(3ChdgG (B:s
(3Yf GdOjhf GdJi JJYdb HgG eWGdHI Gddg JYGdi cOjf GdPchI hOjf GdcaGQI hZjQgG s
(3BNQgG (B:s
(3aGLJeY dGe cd efgeG YTQhf OjfGQkG hdHfJg SJhf hdehdGg YTQI OfGfjQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1247s
Keywords: (3Yde GdaQGFVs